Exploring Tourist Behavior and Sustainability in Island Tourism: A Systematic Literature Review - Ilhamalimy, Ridho Rafqi; Suhud, Usep; Wibowo, Setyo Ferry (Siber International Journal of Digital Business (SIJDB), 2026)
This study aims to explore the relationship between tourist behavior and the sustainability of island tourism through a Systematic Literature Review (SLR) approach based on the PRISMA 2020 protocol. Data were obtained from two main databases, namely Scopus and ScienceDirect, covering publications from 2021–2025. In the initial identification stage, 733 articles were found. After going through the screening, eligibility, and inclusion processes, 53 articles were obtained that met the criteria for further analysis. The analysis was conducted bibliometrically and thematically to map tourist behavior variables, frequently used theories, and the geographical distribution of global research. The results show that the dominanttheories used are the Theory of Planned Behavior (TPB), Service Quality (SERVQUAL), and Social Exchange Theory (SET). The most frequently studied variables include tourist satisfaction, destination loyalty, destination image, and revisit intention. Thematically, the research focuses on three main areas: (1) sustainable practices and environmental awareness, (2) tourist experience, satisfaction, and revisit intention, and (3) destination image, local culture, and loyalty formation. Geographically, publications are dominated by Europe, followed by ASEAN and non-ASEAN Asia. The results of this study provide a conceptualcontribution to strengthening tourist behavior models that support the sustainability of island destinations and enrich the global research direction in the field of sustainable tourism.